Reclaiming our streets: A review of the relationship between race, street safety, and comfort in public places - Sultan, Zenia; van der Jagt, Astara; Cianflone, Amy; Kouzoukas, Erika; Christopher, Gabriella (Prepared by the McMaster Research Shop for Environment Hamilton, 2021)
This report presents the results of a McMaster Research Shop project for Environment Hamilton. This project reviewed research regarding the intersection between race, street safety, and comfort in public places in order to provide Environment Hamilton with suggestions for a street audit tool that focuses on racial equity. Research methods for this project include a literature review and an environmental scan.
Keywords: Hamilton, community-engaged research, racial equity, street planning, street safety